Differentiation of bone marrow-derived mesenchymal stem cells in diabetic patients into islet-like insulin-producing cells: a new era in the treatment of diabetes. Issue 1 (July 2016) - Ghoneim, Mohamed A.; Agina, Hala A.; Elbaz, Mahmoud A.; Emarah, Nashwa M.; Khater, Sherry M.
Abstract : Background: The availability of donors for transplantation of human β-cells as a form of treatment for type II diabetes is limited. Introduction of differentiated human bone marrow-derived mesenchymal stem cells (MSCs) would allow transplantation of an autologous source of β-cells. This would alleviate the limitations of availability and/or allogenic rejection following pancreatic or islet transplantation. Materials and methods: Bone marrow cells were obtained from three adult type II diabetic volunteers and three nondiabetic donors. After 3 days in culture, adherent MSCs were expanded for two passages. At passage 3, differentiation was carried out in a three-staged procedure. Cells were cultured in a glucose-rich medium containing activation and growth factors including B27, betacellulin, activin A, and nicotinamde. These cells were evaluated for endocrine characteristics by flow cytometry and morphology. Differentiated cells were transplanted under the kidney capsule of diabetic nude mice and their diabetic status was tested by oral glucose tolerance tests. Results: Following differentiation, cells expressed the hormones insulin, glucagon, and somatostatin. No differences in cell characteristics were noted between diabetic and nondiabetic donors. Hormones were detectable by immunomicroscopy in some cells. Transplantation into diabetic mice resulted in secretion of human insulin, near-normalization of glucose levels, and improvements in glucose intolerance. When the MSC-bearing kidneys were removed, rapid return of diabetic state was noted. Histology of the removed kidneys identified insulin-positive cells in the graft. Conclusion: Human MSCs from diabetic and nondiabetic donors can be differentiated in vitro to form insulin-producing cells that can restore normoglycemia in diabetic mice. This source of material for autologous transplantation offers new opportunities for the treatment of diabetes.